Identifikasi Morfologi dan Sifat Mekanik Serat Abaka (Musa textilis) Identification of Morphology and Mechanical Properties of Abaca Fiber (Musa textilis) - A.H. Darmawan A; H Onggo; H Judawisastra (Masyarakat Peneliti Kayu Indonesia, 2009)
A research has done on the morphology and mechanical properties of abaca fiber. The investigation of morphology is observed by Scanning Electron Microscope (SEM). Weibull distribution technique is performed to evaluate the variation of fibers strength. And the mechanical properties are tested by using single filament tensile tester (Statimat). The result showed that Abaca is bundle fibers with the diameter of cross-section is about 176 μm. Mechanical strength of fiber is 381 MPa with elongation at break is 1.6 %. And the value of modulus Weibull is 2.69.